Identification of Fly Density in Traditional Markets of Malang City, East Java - Sihabul Fudhula’i, Ari; Al-Irsyad, Muhammad; Novita Deniati, Ema; Annisaa, Annisaa (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2025)
The environment plays a crucial role in the emergence and spread of diseases. Environmental sanitation is particularly essential in public places such as markets, as these locations are frequented by the community on a daily basis. Poor market sanitation conditions can facilitate the breeding of disease vectors, such as flies. Therefore, this study aimed to identify fly density as an indicator of environmental sanitation quality. This research employed an exploratory observational design by observing market environmental conditions and recording the number of flies trapped using a fly grill at four observation points in Traditional Market X, Malang City. The results indicated that temperature and humidity were interrelated and influenced each other. The average fly density at the four observation points ranged from low to moderate and high categories. The beef stall showed a moderate to low category (3.0, 0.6, 0.2); the chicken meat stall showed a low to moderate category (0.2, 1.2, 3.2); the goat meat and fish stall showed a low to high category (1.2, 1.8, 8.8); while the food and beverage stall showed a low category (0, 0, 0.4).